Long-Term Organic–Inorganic Fertilization Regimes Alter Bacterial and Fungal Communities and Rice Yields in Paddy Soil - Ma, Tengfei; He, Xiaohui; Chen, Shanguo; Li, Yujia; Huang, Qiwei; Xue, Chao; Shen, Qirong (Frontiers in Microbiology, 2022)
Microorganisms are the most abundant and diverse organisms in soils and have important effects on soil fertility. In this study, effects of the long-term fertilization treatments no fertilizer (CK), chemical fertilizer (nitrogen–phosphorus–potassium (NPK)), and organic–inorganic fertilizer (NPK and organic fertilizer (NPKM)) on rice yield and soil bacterial and fungal community diversity, structure, composition, and interaction networks were evaluated. Of the three treatments, the highest rice yield was in NPKM. Bacterial richness was significantly higher in NPKM than in NPK. Fertilization treatment significantly altered β diversity of communities, species composition of bacterial and fungal communities, and structure of soil microbial networks. The most complex bacterial and fungal interaction co-occurrence network with the highest average degree and numbers of edges and nodes was in NPKM. Relative abundance of the plant growth-promoting fungus Trichoderma increased significantly in NPKM compared with CK and NPK. The results of the study indicate that bacterial richness and microbial community member interactions (network complexity) might be suitable indicators of soil biological fertility. This research provides new insights on the effects of different fertilization regimes on responses of soil bacterial and fungal communities and their contributions to crop yield. New indicators such as bacterial richness and complexity of microbial interaction networks are also identified that can be used to evaluate soil biological fertility.